(untitled) (Филолошки студии, 2019)
The cultural and historical tradition of a nation is a permanent process with its own development. The momentum of this movement depends on the political and social conditions. In the developing process of material and spiritual culture that have created the tradition of a nation, and among the great number of historical persons that have been involved Arseni Jovkov (1884 -1924) appears as a Macedonian intellectual, bicameral writer, publicist, journalist, photographer and cinematographer, an author of the screenplay of the feature film "Ilinden" and the documentary "Macedonia".